2019
DOI: 10.1503/cjs.005018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Roux-en-Y gastric bypass on pharmacologic dependence in obese patients with type 2 diabetes

Abstract: Background: More than half the diabetes-related health care costs in Canada relate to drug costs. We aimed to determine the effect of Roux-en-Y gastric bypass (RYGB) on the use of insulin and orally administered hypoglycemic medications in patients with diabetes. We also looked to determine overall cost savings with the procedure. Methods: We reviewed the bariatric clinic records of all patients with a confirmed diagnosis of type 2 diabetes mellitus who underwent RYGB between 2010/11 and 2014/15. Percentage es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Previous research suggests that bariatric surgery is an effective treatment for improvement of T2DM in obese patients. 9 Several studies, including multiple randomised control trials demonstrate that bariatric surgery is effective for weight loss and remission of T2DM and metabolic syndrome when compared with medical therapy alone in the overall population. 9–20 A study with Australian Indigenous populations demonstrated a 66% diabetes remission rate following gastric banding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research suggests that bariatric surgery is an effective treatment for improvement of T2DM in obese patients. 9 Several studies, including multiple randomised control trials demonstrate that bariatric surgery is effective for weight loss and remission of T2DM and metabolic syndrome when compared with medical therapy alone in the overall population. 9–20 A study with Australian Indigenous populations demonstrated a 66% diabetes remission rate following gastric banding.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Several studies, including multiple randomised control trials demonstrate that bariatric surgery is effective for weight loss and remission of T2DM and metabolic syndrome when compared with medical therapy alone in the overall population. 9–20 A study with Australian Indigenous populations demonstrated a 66% diabetes remission rate following gastric banding. 21 Although literature relating to Canada’s Indigenous bariatric surgery population is scarce, available research suggests that surgery is safe and effective, and this patient group may respond better to the intervention based on higher resolution rates of obesity-related comorbidities.…”
Section: Introductionmentioning
confidence: 99%